2023
DOI: 10.3390/ijms242417429
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Regional Pro-Adrenomedullin Can Predict Organ Failure and Prognosis in Sepsis?

Silvia Spoto,
Stefania Basili,
Roberto Cangemi
et al.

Abstract: Sepsis causes immune dysregulation and endotheliitis, with an increase in mid-regional pro-adrenomedullin (MR-proADM). The aim of the study is to determine an MR-proADM value that, in addition to clinical diagnosis, can identify patients with localized infection or those with sepsis/septic shock, with specific organ damage or with the need for intensive care unit (ICU) transfer and prognosis. The secondary aim is to correlate the MR-proADM value with the length of stay (LOS). In total, 301 subjects with sepsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…This evidence underscores the crucial functions of ADM and the importance of information on the degree of endothelitis and dysregulation of the ADM system provided by the ADM and/or MR-proADM assay [ 4 , 120 , 121 , 122 , 123 ]. Indeed, the value of MR-proADM, which correlates directly with the extent of organ damage, indicates organ dysfunction, disease severity, diagnosis and prognosis in patients with severe viral and bacterial infections [ 4 , 120 , 121 , 122 , 123 ].…”
Section: Pathophysiology Of Endothelitis: Adrenomedullin Expressionmentioning
confidence: 82%
See 3 more Smart Citations
“…This evidence underscores the crucial functions of ADM and the importance of information on the degree of endothelitis and dysregulation of the ADM system provided by the ADM and/or MR-proADM assay [ 4 , 120 , 121 , 122 , 123 ]. Indeed, the value of MR-proADM, which correlates directly with the extent of organ damage, indicates organ dysfunction, disease severity, diagnosis and prognosis in patients with severe viral and bacterial infections [ 4 , 120 , 121 , 122 , 123 ].…”
Section: Pathophysiology Of Endothelitis: Adrenomedullin Expressionmentioning
confidence: 82%
“…Furthermore, MR-proADM acts as a biomarker for sepsis, reflecting the degree of oxidative stress and indicating the severity of the condition in line with organ damage and prognosis [ 120 , 124 ]. From a clinical perspective, MR-pro-ADM can accurately detect patients with one or multiple organ failures, particularly showing a stronger correlation for certain variables such as acute kidney injury (AKI), GCS < 15, and the requirement for intensive care unit (ICU) transfer indicating a more severe prognosis [ 19 , 20 , 120 , 125 , 126 , 127 , 128 , 129 ].…”
Section: Pathophysiology Of Endothelitis: Adrenomedullin Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…A new study reported that we identi ed a dynamically changing haematological-immunological pro le of sepsis, including lymphopenia, reduced dendritic cell frequency and myeloid HLA-DR expression, even though C-reactive protein, a common clinical marker of in ammation, is not elevated, which is characteristic of sepsis [8]. Mid-region adrenomedullinogen (MR-proADM) is a marker of infection-induced oxidative stress, re ecting severity proportional to organ damage [9].Elevated C-reactive protein to albumin ratio (CAR) is associated with increased mortality and poor prognosis in patients with sepsis [10]. The neutrophil index (DNI) has shown better validity in differentiating septic febrile patients from non-septic febrile patients [11].…”
Section: Introductionmentioning
confidence: 99%